Potential of dihydropyrimidine dehydrogenase genotypes in personalising 5-fluorouracil therapy among colorectal cancer patients - Ngow, Harris Abdullah; Lay , Kek Teh; Hamzah, Sharina; Hashim, Hazwanie; Bannur, Zakaria; Zakaria, Zainul Amiruddin; Hasbullani, Zakaria; John Kwong, Siew Shia; Henry, Fijeraid; Md Nor, Azmid; Zailani, Mohd; Prabu, Ramasamy; et al. (International Association of Therapeutic Drug Monitoring and Clinical Toxicology, 2011)
Background: Dihydropyrimidine dehydrogenase (DPD) is a pyrimidine catabolic enzyme involved in the initial and rate-limiting step of the catabolic pathway of toxic metabolites of 5-fluorouracil (5-FU). Several studies have reported that deficiency of DPD and polymorphisms of its gene are related to 5-FU toxicities and death. Association between serum concentration of 5-FU and its related toxicity has also been previously demonstrated. Hence, this study aims to understand the role of DPYD variants in serum level of 5-FU and the risk of developing toxicity to prevent adverse reactions and maximize therapy outcome for personalized medicine.